Semi-rational engineering membrane binding domain of L-amino acid deaminase from Proteus vulgaris for enhanced α-ketoisocaproate - Song, Yang; Wang, Rui; Zhang, Zixuan; Liu, Xinran; Qi, Lulu; Shentu, Xuping; Yu, Xiaoping (Frontiers in Microbiology, 2022)
α-Keto acids are important raw materials for pharmaceuticals and functional foods, which could be produced from cheap feed stock by whole cell biocatalysts containing L-amino acid deaminases (L-AADs). However, the production capacity is limited by the low activity of L-AADs. The L-AAD mediated redox reaction employs the electron transport chain to transfer electrons from the reduced FADH2 to O2, implying that the interaction between L-AAD and the cell membrane affects its catalytic activity. To improve the catalytic activity of L-AAD from Proteus vulgaris, we redesigned the membrane-bound hydrophobic insertion sequences (INS, residues 325-375) by saturation mutagenesis and high-throughput screening. Mutants D340N and L363N exhibited higher affinity and catalytic efficiency for L-leucine, with half-life 1.62-fold and 1.28-fold longer than that of wild-type L-AAD. D340N catalyzed L-leucine to produce 81.21 g·L-1 α-ketoisocaproate, with a bioconversion rate of 89.06%, which was 17.57% higher than that of the wild-type. It is predicted that the mutations enhanced the interaction between the protein and the cell membrane.